Warming from cold pools: A pathway for mesoscale organization to alter Earth’s radiation budget - Pouriya Alinaghi; Martin Janssens; Fredrik Jansson (Proceedings of the National Academy of Sciences, 2025)
Marine shallow cumulus clouds have long caused large uncertainty in climate projections. Such “trade cumuli” frequently organize into mesoscale (10 to 500 km) structures, through two processes that couple the clouds to shallow mesoscale circulations: i) mesoscale moisture aggregation and ii) cold pools, driven by mesoscale rain evaporation beneath the mesoscale cloud structures. Since global climate models do not capture these mesoscale processes, while the degree of mesoscale organization is observed to correlate to shortwave cooling, it has been suggested that mesoscale processes modulate contemporary estimates of cloud response to global warming. Here, we show that introducing mesoscale dynamics can indeed substantially alter top-of-the-atmosphere radiative budget, if the balance between the two circulations is upset. By homogenizing mesoscale rain evaporation patterns, we suppress the formation and effects of cold pools in a large ensemble of large-domain, large-eddy simulations. The experiments reveal that cold pool dynamics reduce mesoscale ascent in the cloud systems, thereby arresting a runaway self-aggregation of moisture into very moist, cloudy regions that occurs without them. This reduces the net rainfall of the cumulus fields, moistens the cloud layer and thus reduces the emission of clear-sky longwave radiation to space, giving an ensemble-averaged warming of 1.88 W/m 2 . Our results highlight that the proper interplay between mesoscale processes is critical for capturing radiative budgets-especially in kilometer-scale climate models that only partially resolve shallow cumulus aggregation and cold pools.